Media and Information Literacy in the Age of Algorithms: Empowering Icelandic Students to Critically Engage with Algorithmically Curated Content and the Challenges of Misinformation - Jakob Sturla Einarsson 1991- (2025)
As algorithmically curated content increasingly shapes what young people see, search for, and share online, the need to equip students with the skills to engage critically with digital media has become urgent, particularly in the face of growing misinformation. This paper addresses two central questions about algorithm literacy within the broader framework of media and information literacy (MIL), focusing on educational contexts in Iceland: How can education systems foster the skills necessary for teenagers to critically engage with algorithmically curated content and identify misinformation? And how well is the Icelandic education system equipped to nurture these competencies? Drawing on curriculum analysis, international frameworks, and recent studies on youth media habits and algorithmic awareness, the findings suggest that while elements of MIL are present in Iceland’s curriculum, algorithm literacy—and its connection to the spread of misinformation—remains underdeveloped. Strengthening students’ ability to engage critically with digital environments requires not only technical skills but also an understanding of how content is selected and presented. Incorporating algorithm literacy into existing educational structures could enhance media awareness, critical thinking, and resilience to misinformation. By highlighting gaps in curriculum, policy, and research, this study contributes recommendations for improving educational practices and points to areas that warrant further investigation.